KARAKTERISTIK DAN KERAPATAN SARANG ORANGUTAN (PONGO PYGMAEUS WURMBII) DI HUTAN DESA BLOK PEMATANG GADUNG KABUPATEN KETAPANG PROPINSI KALIMANTAN BARAT - Sidiq, Muhammad; Nurdjali, Bachrun; Idham, M (Universitas Tanjungpura, 2015)
Orangutan (Pongo pygmaeus wurmbii) are protected from Indonesian rule whose existence is increasingly threatened with extinction, some of the main threats faced of orangutan (Pongo pygmaeus wurmbii) is lost habitat, illegal logging, forest fires, poaching and trade. Village Forest Blok Pematang Gadung is an area of â€‹â€‹potential place for animals to live in it but on the other hand gold mining unlicensed also take advantage of the place. In defending the life of orangutan in the place needed information about the characteristics and density of orangutan nests to be used as reference for the development, management, protection and conservation as well as information the planning or monitoring, in order to take appropriate actions in the preservation of orangutan (Pongo pygmaeus wurmbii). Orangutan nests density is influenced by the distribution of orangutan which depend on the condition of orangutanÂ feeding, habitat conditions and access to females (reproduction), orangutan will build a nest in accordance to the weight of body and adjusting the structure of the forest, the most frequently encountered of orangutan nests class is class C while a position which is often used to make orangutan nests are positions 1 and 2, which is a very safe position because it is located in the branching tree and protected by tree crowns so orangutan can be protected from hot weather, wind or rain. Keyword : Characteristic, Density, Orangutan nest, Pematang gadung.